Real-Night-time Road Sign Detection by the Use of Cascade Object Detector - Shahbaz, Shahad J.; Al-Zuky, Ali A. D.; Al-Obaidi , Fatin E. M. (Iraqi Journal of Science, 2023)
Variations in perspective, illumination, motion blur, and weatherworn degeneration of signs may all be essential factors in road-sign identification. The current research purpose is to evaluate the effectiveness of the image processing technique in detecting road signs as well as to find the appropriate threshold value range for doing so. The efficiency of the cascade object detector in detecting road signs was tested under variations of speed and threshold values. The suggested system involved using video data to calculate the number of frames per second and creating an output file that contains the specified targets with their labels to use later in the final process (i.e., training stage). In the current research, two videos captured some types of traffic signs (40, 60, 80, and cross signs) in Palestine and Al-Rubaie streets during night time in Baghdad city. The practical significance is demonstrated here by using the optimal threshold value for more accurate object detection. Through an increase in threshold values, results show that the highest precision value, which is equal to one, occurred for crossroad sign relations with stable behavior, followed by 80 (i.e., 1-0.824) and 60-speed signs (i.e., 1-0.315), respectively, with positive relationships, and ended by speed sign 40, which witnessed a reverse relationship with increasing threshold values until the breakdown case took place, which usually occurred above the threshold value equal to thirty (i.e., 0.471-0.134).